WHAT FACTORS INFLUENCE THE WELFARE OF ZAKAT BENEFICIARIES? - Ayuniyyah, Qurroh; Hambari,; Hakiem, Hilman; Faisal, Ahmad (Journal of Islamic Monetary Economics and Finance, 2025)
This study investigates the influence of demographic, social, and economic variables on the welfare of zakat beneficiaries in West Java, Indonesia. Using a sample of 1,300 zakat beneficiaries, the paper applies the Chi-square Automatic Interaction Detector (CHAID) method. Our findings suggest the crucial role of monitoring by amil institutions in the respective areas on the improvement of material and spiritual conditions of zakat beneficiaries. The study suggests that amil plays a major part in the success of zakat distribution programs and the programs should be further enhanced for the betterment of zakat beneficiaries. This study also shows that apart from zakat distribution programs, there are also some demographic, social, and economic variables that affect the income and spiritual conditions of zakat beneficiaries.